Historiese perspektiewe op die kerklik-teologiese opieiding van die Nederduitsch Hervormde Kerk aan die Universiteit van Pretoria - Pont, A. D. (Hervormde teologiese studies, 1994)
Historical perspectives on the theological training of ministers of the Nederduitsch Hervormde Kerk van Afrika at the University of Pretoria In commemorating the establishment of the theological faculty of the Nederduitsch Hervormde Kerk in 1917 at the old Transvaal University College, the forerunner of the University of Pretoria, some historical perspectives are given. In the first place the revised duplex ordo that marked the initial structur; of the faculty is discussed. With the advent and participation of the Nederduitsch Hervormde or Gereformeerde Kerk in the theological faculty, there was a gradual move to a simplex ordo, which was finally achieved in 1952. Concluding remarks are made about the theological intent of the faculty from 1917-1992.